A redescription of Protolimnesia longa Besch, 1963 from Bolivia, with the first description of the female (Acari: Hydrachnidia: Limnesiidae) - Pešić, Vladimir; Smit, Harry; Datry, Thibault (Zootaxa, 2016)
The water mite genus Protolimnesia Lundblad, 1927 is distributed in South and Central America, the Caribbean (Haiti) and southern parts of the USA (Goldschmidt 2004). One odd record is known from Oman (Smit & Pešić 2010). In addition to the nominate subgenus, the genus also includes Protolimnesella Cook, 1980 and Voldroguella Cook, 1981, typical inhabitants of interstitial habitats (Goldschmidt 2004). The nominate subgenus includes seven species and subspecies, most of them are stream-dwellers, but Protolimnesia longa Besch, 1963 appears to be a characteristic inhabitant of the interstitial of intermittent streams. This species was described by Besch (1963) based on a single male from the interstitial of a dry stream at 1200 m altitude in Argentina. Since then, no further records of this species were published. In the original description Besch (1963) illustrated only the ventral and dorsal side. Smit (2002) and Goldschmidt (2004) re-examined the holotype of P. longa deposited in the Viets Collection (SMF) and provided illustrations of the palp and ejaculatory complex, respectively. However, some important characteristics are neither given in the original description nor are visible in the type material. Smit (2002) mentioned that both fourth legs in the holotype slide are positioned in such a way that examination of the claws of IV-L-6 is not possible, Goldschmidt (2004) stated that the ejaculatory complex in the type is mounted laterally and most probably squashed.